(untitled) (Fiep Bulletin - online, 2013)
The Gymnastics began to be understood as a major tool in improving the physical health of the employee reducing and preventing occupational problems. For (HARTMANN et al, 2008). The Regional Labor Court of Alagoas 19th Region concerned about the welfare of mankind in all its aspects, seeks to provide response mechanisms to prevent and minimize the consequences of various postural defects, injuries, occupational repetitive strain (RSI), structures that are degenerative and cumulative preceded by any pain or discomfort and even work-related disorders (MSDs), since we are aware that the body can not be separated from the mind, as it will only be complete and in full harmony, if running perfectly as a whole, in a single unit. Objective: This study aimed to evaluate the movements of flexion and extension of the wrist magistrates/servers Regional Labor Court of the 19th Region Alagoas participating in gymnastics classes. Methodology: The sample consisted of 159 magistrates/servers males aged 21-61 years (X = 42.30 years), and 148 magistrates/servers females aged 20 to 64 years (X = 41.60 years) of the Regional Labor Court of the 19th Region Alagoas. For data collection test was performed flexion and extension of the wrist joint proposed by Dantas (2003). Data analysis was made through the table proposed by the AMERICAN MEDICAL ASSOCIATION (1995) apud Dantas (2003). Conclusion: The analysis and discussion of the data obtained, it was found in general that the magistrates/servers are within international standards of normality according to the parameters proposed by the American Medical Association, (1995).